Isolation and characterization of fluorescence-enhancing RNA tags - Wiesmayr, Anna; Jäschke, Andres (Bioorganic & medicinal chemistry, 2011)
Methods for the visualization of RNAs are urgently needed for studying a wide variety of cellular processes. Here we report on-bead screening of RNA libraries and its application to the isolation of specific fluorescence-enhancing RNA sequences. A one-bead-one-compound combinatorial RNA library with over one million different sequences was synthesized using the split-and-mix method. Solid-phase synthesis of 30 mer RNAs was performed on 15μm and 60μm diameter polystyrene beads bearing a non-cleavable linker. The RNA-derivatized beads were incubated with the well-established FlAsH pre-fluorophore and then screened for fluorescence enhancement, either by manually picking the brightest beads under a fluorescence microscope or by sorting with a FACS instrument. A protocol was established for sequence determination from single beads. While numerous RNA sequences showed increased fluorescence when immobilized, only few of them influenced the fluorescence properties of the FlAsH dye when detached from the beads. One of these sequences was found to induce a bathochromic shift in the excitation (from 492 to 510nm) and emission (from 512 to 523nm) maxima. This shift was accompanied by a 3.6-fold fluorescence enhancement of FlAsH fluorescence intensity. Mutation studies on the sequence revealed a rather robust structural motif.
Available online 12 August 2010
Gesehen am 03.11.2022